2016
DOI: 10.1039/c5nr09112h
|View full text |Cite
|
Sign up to set email alerts
|

Breakable mesoporous silica nanoparticles for targeted drug delivery

Abstract: "Pop goes the particle". Here we report on the preparation of redox responsive mesoporous organo-silica nanoparticles containing disulfide (S-S) bridges (ss-NPs) that, even upon the exohedral grafting of targeting ligands, retained their ability to undergo structural degradation, and increase their local release activity when exposed to a reducing agent. This degradation could be observed also inside glioma C6 cancer cells. Moreover, when anticancer drug-loaded pristine and derivatized ss-NPs were fed to gliom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
141
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 196 publications
(142 citation statements)
references
References 49 publications
1
141
0
Order By: Relevance
“…The semi-transparency of biological tissue in the window 700-1000 nm makes this range particularly appealing for optical probes of analytes with absorption (and/or luminescence) in this range, as well as for photothermal and photodynamic therapeutic applications which may rely on photo-activation of particular drugs (e.g. to open cages containing suitable drugs in place of "redox-driven" breaking mechanisms), [15] or for therapy of sensitive tumours, [16] or even atherosclerosis treatment. [17] NIR LEDs are often used also in security authentication technologies exploiting biometrics, such as imaging of finger veins [18] and iris recognition.…”
Section: Opportunities and Challenges 21 Application Areas Of Nir Emmentioning
confidence: 99%
“…The semi-transparency of biological tissue in the window 700-1000 nm makes this range particularly appealing for optical probes of analytes with absorption (and/or luminescence) in this range, as well as for photothermal and photodynamic therapeutic applications which may rely on photo-activation of particular drugs (e.g. to open cages containing suitable drugs in place of "redox-driven" breaking mechanisms), [15] or for therapy of sensitive tumours, [16] or even atherosclerosis treatment. [17] NIR LEDs are often used also in security authentication technologies exploiting biometrics, such as imaging of finger veins [18] and iris recognition.…”
Section: Opportunities and Challenges 21 Application Areas Of Nir Emmentioning
confidence: 99%
“…356 Some work has been done to ease the degradation 357 of nanoparticles once they have performed their 358 function. Maggini et al [58] recently reported 359 breakable MSNs by introducing redox-cleavable 360 disulphide bonds inside the silica network that 361 induced the loss of particle structure when exposed 362 to a reducing environment (like the intracellular 363 medium). This particle self-destruction would then 364 facilitate the degradation and excretion of the 365 resulting smaller particles.…”
Section: Chemical Compositionmentioning
confidence: 99%
“…Gene transfection efficiency is affected by both the level of cellular uptake and the ability to escape from endosomal compartments . Colocalization studies were conducted to investigate the distribution of Gal‐micelles inside the cells using the Z‐stack technique . Phalloidin Alexa Fluor 647 and LysoTracker Deep Red were used to stain cytoskeleton and acidic organelles, respectively.…”
Section: Resultsmentioning
confidence: 99%